Integrating corporate social responsibility dimensions and product innovation in firms in the Ghanaian insurance industry - Ghansah, Kyeame; Jagannathan, Uday Kumar (The Economics and Finance Letters, 2025)
This study evaluates how Corporate Social Responsibility (CSR) dimensions affect product innovation performance in Ghanaian insurance companies. The study clarifies which dimensions of CSR (i.e. Economic, Legal, Ethical, and Philanthropic Responsibilities) are most influential in driving innovation performance and the effect of their combined interactions. Survey data of 389 employees from 49 insurance companies in Ghana were analyzed using Partial Least Squares Structural Equation Modelling (SEM). SEM was conducted after confirmatory factor analysis confirmed the reliability and validity of the constructs. Bias-corrected bootstrapping was used to assess the direct and moderated path relationships. The results showed that Economic CSR (β = 0.341, p < 0.05), Legal CSR (β = 0.143, p < 0.05), and Ethical CSR (β = 0.219, p < 0.05) were positive determinants of insurance product innovation performance. Economic CSR × Philanthropic CSR → Product Innovation (β = 0.113, p < 0.05) and Legal CSR × Ethical CSR → Product Innovation (β = 0.177, p < 0.05) were significant moderating relationships. The other four-way interactions were non-significant. The result shows that, although Economic CSR, Legal CSR, and Ethical CSR individually affect product innovation, their interactions produce positive outcomes for insurance companies. The combined synergies arising from the interactions create environments that enhance the positive outcomes of product innovation over single impacts. This implies that firms should craft their CSR strategies to exploit cross-dimensional complementarities. Focusing on integrated CSR dimensional strategies can unlock greater innovative capacity in the insurance industry.